2023
DOI: 10.2147/prbm.s400058
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Big Five and Trait Emotional Intelligence Among College Students

Abstract: Purpose Personality traits are relatively stable and may influence various aspects of human behavior. Trait emotional intelligence (Trait EI) presents the non-cognitive element of intelligence. Trait EI also enables individuals to deal with different stressors of life. Thus, understanding the relationship between personality traits and Trait EI can be beneficial. The current study explores the role of the big five personality factors in influencing Trait EI. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…First, this study explores the internal connection between GI and PTG based on the relationship between people and the collective and people and society, which enriches the research on the formation mechanism of PTG in the post COVID-19 era and provides a new perspective for future research. Second, this study further enriches the research on SEC in promoting physical and mental health of adolescents, which can help adolescent groups improve their SEC to help them better understand and cope with the emotional needs of others 116 and thus better cope with their own trauma, which also supports and to some extent deepens social identity theory and emotional intelligence theory. Finally, this study is the first to consider the relationship between the three, which provides new and revealing ideas for understanding the processes and mechanisms of PTG.…”
Section: Discussionmentioning
confidence: 57%
“…First, this study explores the internal connection between GI and PTG based on the relationship between people and the collective and people and society, which enriches the research on the formation mechanism of PTG in the post COVID-19 era and provides a new perspective for future research. Second, this study further enriches the research on SEC in promoting physical and mental health of adolescents, which can help adolescent groups improve their SEC to help them better understand and cope with the emotional needs of others 116 and thus better cope with their own trauma, which also supports and to some extent deepens social identity theory and emotional intelligence theory. Finally, this study is the first to consider the relationship between the three, which provides new and revealing ideas for understanding the processes and mechanisms of PTG.…”
Section: Discussionmentioning
confidence: 57%
“…It should not be surprising that feeling types are more emotionally sensitive, though this may not always be advantageous in the work setting Over the years, various studies have related other personality measures, mainly the Big Five to measures of emotional intelligence (Alegre et al, 2019;Petrides et al, 2010;Veselka et al, 2009). In a recent study, Kumar and Tankha (2023) confirmed the results of many other studies noting that Neuroticism was a negative and most significant predictor of trait EI. This comes as no surprise because emotional regulation is at the heart of Neuroticism/Stability, and it is not measured in the MBTI.…”
Section: Meanmentioning
confidence: 58%
“…For the purposes of this research the Five Factor Model (also known as the “Big 5”) personality test ( 35 ) is used for measuring the participant's level of neuroticism. This has been suggested to be related to the level that negative emotions affect an individual during training ( 36 38 ). The feedback provided to the participant as well as the virtual patient's emotional state is affected by both these elements.…”
Section: Design Of the Online Learning Environmentmentioning
confidence: 99%